Bronchopulmonary pharmacokinetics of (R)‐salbutamol and (S)‐salbutamol enantiomers in pulmonary epithelial lining fluid and lung tissue of horses. (8th February 2017) - Jacobson, Glenn A.; Raidal, Sharanne; Robson, Kate; Narkowicz, Christian K.; Nichols, David S.; Haydn Walters, E.
Abstract : Aims: Salbutamol is usually administered as a racemic mixture but little is known about the enantioselectivity of salbutamol pharmacokinetics in the lung. This study was designed to investigate enantiomer concentrations in lung tissue after inhaled dosing. Methods: Horses ( n = 12) received racemic salbutamol 1000 μg via inhalation. Enantioselective ultra performance liquid chromatography–tandem mass spectrometry was used to determine salbutamol concentrations in pulmonary epithelial lining fluid (PELF) sampled 2, 5, 10 and 15 min after administration, in central lung (endoscopic bronchial biopsy) and peripheral lung (percutaneous pulmonary biopsy) tissues (at 20 and 25 min respectively), and in plasma samples. Results: Mean ± 95% confidence interval (CI) yield of PELF was 57 ± 10 mg. Initial mean ± 95%CI (R)‐ and (S)‐salbutamol PELF concentrations were 389 ± 189 ng g –1 and 378 ± 177 ng g –1 respectively, and both reduced approximately 50% by 15 min. Mean ± 95%CI central lung levels of drug were higher than peripheral lung tissue for both (R)‐salbutamol (875 ± 945 vs. 49.5 ± 12 ng g –1 ) and (S)‐salbutamol (877 ± 955 vs. 50.9 ± 12 ng g –1 ) respectively. There was no evidence of enantioselectivity in PELF or central lung but minor ( 2%) enantioselectivity was observed in the peripheral lung. Enantioselectivity was clearly evident in plasma with (S):(R) ratio of 1.25 and 1.14 for both area under the concentration–time curve (0–25 min) and Cmax respectively. Conclusions: PELF sampling in horses offers sufficient yield allowing direct detection of drug and, combined with tissue sampling, is a valuable model to investigate bronchopulmonary pharmacokinetics. Salbutamol did not demonstrate enantioselectivity in PELF or central lung tissue uptake following acute dosing, however, enantioselective plasma concentrations were demonstrated, with minor enantioselectivity in the peripheral lung.